An Unusual Ulcer. (December 2018) - Bilancini, Salvino; D'amati, Giulia; Cerbelli, Bruna; Lucchi, Massimo
This clinical case describes a 78-year-old female patient who underwent total thyroidectomy and parathyroidectomy due to thyroid cancer; surgery was followed by radioiodine therapy. The patient was treated with 20 µg of teriparatide once a day for 7 years and consistently showed above normal blood calcium levels. In addition, following the operation, the patient began taking 50 000 units of vitamin D orally every month and 1 g of calcium per os a day. A painful eschar had appeared on the front of her left leg 3 months before; it had developed into a deep, painful ulcer. The patient did not present arterial or venous diseases. Arterial hypertension was effectively managed with 5 mg of ramipril per day, renal function was normal, and the patient was not suffering from diabetes. A computed tomography scan gave evidence of extensive dermo-hypodermitis calcification in the ulcer area. A biopsy was performed and the histological examination revealed calciphylaxis. The patient was treated by suspending teriparatide, which actually had been suspended months before, and replacing it with bisphosphonate; suspension of calcium and vitamin D and the oral administration of 250 units of sulodexide every 12 hours. Local therapy was adapted according to the advancement of the ulcer's stages. This case represents one of non-uremic calciphylaxis determined by an overly lengthy administration of a parathyroid hormone that caused drug-induced hyperthyroidism over a long period of time. A revision of the worldwide literature on the topic was carried out and an etiopathogenetic hypothesis concerning the clinical case is put forward.